Affirmative action in plural societies international experiences - Brown, Graham K.; Langer, Arnim; Stewart, Frances 1940- (Palgrave Macmillan, 2012)
Global contributors discuss the theoretical controversies concerning the merits and demerits of affirmative action, and explain why affirmative action is needed in multi-ethnic countries. They analyze actual experience with affirmative action policies - their origin, nature and consequences - in nine countries